THE ROLE OF POLYMORPHISM OF LIPID METABOLISM GENES IN THE PATHOGENESIS OF PREECLAMPSIA - Артем Алексеевич Денисов; Анастасия Константиновна Петриченко; Надежда Васильевна Башмакова; Татьяна Борисовна Третьякова; Наталья Борисовна Давыденко; Людмила Анатольевна Пестряева (Мать и дитя в Кузбассе, 2023)
Violation of lipid metabolism with the formation of atherogenic factors and subsequent endothelial dysfunction is one of the concepts explaining the pathogenesis of preeclampsia.